The Role of Household Wealth in Combining Child School and Child Labor: Evidence from MICS Balochistan (Pakistan) - Nawab, Tabish; Aktaş, Beyza Nur; Ahmad, Tusawar Iftikhar; Ibraheem, Ruqayya (iRASD Journal of Economics, 2021)
The issue of combining school & work has taken considerable focus in the past years from policymakers, advocates and researchers. In the literature, the role of household wealth, combining school & work is still an unresolved issue. The researchers have contradicting views about the impact of household wealth on combining child school & work. Child labor and low schooling attendance are found pervasive issues worldwide, particularly in developing countries. This study aims to explore the impact of household wealth on combining child school & work, particularly focusing on the wealth index of the household. For this purpose, microdata having 18471 observations from Multiple Indicator Cluster Survey Balochistan (2010) has been utilized. The binary logistic model has been applied for the children (5-15 years) activity whether they are combining school & work or not. The main finding of this paper is the wealth status of households which has a statistically significant and positive influence on combining child school & work. Both mother and father’s education is positively associated with combining school & work. In addition, mother and father being alive played a vital role in their children’s combined activities of schooling & work rather than doing nothing because the expectations of child schooling are high in parent’s lives. Furthermore, gender, age of the child, and area of residence are positive effects combining school & work. The children from urban zones are more likely to be involved in combining school & work. The policy of this paper suggests that education is the key to break child labor in society by providing education facilities for both girls and boys equally. In addition to policy recommendations, there should be crucial steps to provide a better economic environment for the well-being of the masses to enhance their economic condition especially in rural and deprived areas of Balochistan, and the applicability of child labor laws needs to be focused on. Keywords: